Counter-storytelling, metaphors, and rhetorical questioning: discursive strategies of advocacy toward racial equity in school board meetings. Issue 2 (4th March 2023) - Sampson, Carrie; Bertrand, Melanie
ABSTRACT: Minoritized communities have long engaged in collective resistance against racism and other forms of injustice in schools. In this article, we highlight the discursive strategies of one such case of resistance during official public comments in a series of school board meetings over nine months. Specifically, we identify how community advocates used metaphors, counter-storytelling, and rhetorical questioning to speak out against racism directed largely at Black students in a majority white school district in the US Southwest. We conclude with implications for other communities to consider these strategies in their own resistance and for educators to take seriously the discourse of minoritized communities.